ASARA-A technology-driven maternal and child healthcare model of Araku - Venkatesh Babu, Kirthana; Ravi, Shilpa; Turlapathi, Swarnalatha; Bhaskar, Kalla (International Journal Of Community Medicine And Public Health, 2024)
Tribal populations form 8.6% of total India’s population. The health indicators of tribal populations lag behind their non-tribal counterparts. Limited access to healthcare services, poor transportation facilities, increased out-of-pocket expenditures for health, distinct cultural practices and remote settlement among many others contribute to the poor health status of the tribal populations. However, to achieve sustainable development goals by 2030, it is extremely important to address the healthcare needs of the tribal population. The current paper is the first part of the model of care working paper series that discusses the components of the ASARA project to highlight the impacts of the decade long efforts towards improving maternal and child care in the region.